α-Defensin HD5 Stabilizes Human Papillomavirus 16 Capsid/Core Interactions - Neetu M. Gulati; Masaru Miyagi; Mayim E. Wiens; Jason G. Smith; Phoebe Stewart (Pathogens and Immunity, 2019)
Background: Human papillomavirus (HPV) is linked to nearly all cases of cervical cancer. Despite available vaccines, a deeper understanding of the immune response to HPV is needed. Human α-defensin 5 (HD5), an innate immune effector peptide, blocks infection of multiple serotypes of HPV, including high-risk HPV16. While a common mechanism of α-defensin anti-viral activity against nonenveloped viruses such as HPV has emerged, there is limited understanding of how α-defensins bind to viral capsids to block infection.